Biochemical alternations in leaves of grapevine (Vitis vinifera L.) under virus-induced stress - Sultanova, Nargiz (Acta agriculturae Slovenica, 2025)
Grapevine leafroll disease (GLD) is one of the most prevalent and economically significant viral diseases affecting grapevines. This study aimed to detect GLRaV presence in grapevine cultivars from Azerbaijan and examine associated stress-related metabolic alterations. During the summer of 2023, a total of forty-eight symptomatic grapevine leaf samples were collected from vineyards in Salyan and Jalilabad regions. Visual symptoms included leaf rolling, interveinal reddening, mosaic patterns, and yield decline. Virus detection was performed using serological techniques (AgriStrip and DAS-ELISA) and molecular testing via RT-PCR. Results showed that 13% of samples were infected with GLRaV-2 and 23% with GLRaV-3. Biochemical profiling revealed increased malondialdehyde (MDA) accumulation, indicating elevated lipid peroxidation and oxidative stress in infected vines. Furthermore, significantly higher levels of total phenolic compounds, tocopherols, and soluble proteins were observed, suggesting enhanced non-enzymatic antioxidant responses. The activities of key antioxidant enzymes—superoxide dismutase (SOD), catalase (CAT), and ascorbate peroxidase (APX)—were markedly upregulated in virus-infected samples compared to healthy controls. These enzymatic changes highlight the grapevine’s biochemical defense response to viral stress. Overall, the study demonstrates that GLRaV infection triggers both enzymatic and non-enzymatic antioxidant systems, which may serve as potential biomarkers for virus tolerance in grapevines.
Keywords: ascorbate peroxidase (APX); askorbat peroksidaza (APX); bolezen zvijanja listov vinske trte; catalase (CAT); grapevine leafroll disease; katalaza (CAT); lipid peroxidation; lipidna peroksidacija; superoksid dismutaza (SOD); superoxide dismutase (SOD); tocopherols; tokoferoli